Moving images: Psychoanalytically informed visual methods in documenting the lives of women migrants and asylum seekers. (January 2014) - Haaken, Janice K; O'Neill, Maggie
While feminist arts-based projects have gained legitimacy, theory guiding the use of visual images in field research has lagged. Drawing on psychoanalytic-feminist theory and participatory action research methods, the article presents a study carried out with women refugee and asylum seekers that focuses on their experiences in seeking a place of safety in the United Kingdom. The aim was to produce through photography and videography a collective account of asylum as a daily process. In discussing the study, the authors provide a psychoanalytic framework for working through ethical, political, and methodological dilemmas in the use of visual imagery in feminist research.